Effects of coupling port water injection and EGR on the spray water evolution, combustion and emission of a premixed stoichiometric natural gas engine: A numerical study. (15th September 2022) - Wei, Xiaofei; Qian, Yejian; Meng, Shun; Hua, Yang; Qiu, Liang; Sun, Yu; Wan, Juye; Zhang, Xuelong
Highlights: Effects of coupling PWI and EGR on the stoichiometric natural gas engine were investigated numerically. PWI with 44 mg and 14.4% EGR water has the only effect on the charge density of the manifold. PWI with 220 mg water shows a more significant impact on in-cylinder combustion characteristics. There is an optimal proportion of coupling PWI and EGR for the combustion of the engine. The mass of NO x emission is opposite with the mass of injection water increased. Abstract: To quantitatively analyze the effects of coupling port water injection (PWI) and exhaust gas recirculation (EGR) on the spray water evolution, combustion and emissions for the stoichiometric natural gas engines, five cases were tested on the validation model with 18%EGR (no water), 44 mg water and 14.4% EGR, 110 mg water and 9% EGR, 176 mg water and 3.6% EGR, 220 mg water (no EGR). The results showed that above 43% of injection water formed the film on the engine wall at intake valve closing (IVC). The evaporation rate gradually declined with the increased mass of spray water. The temperature of intake manifold was simultaneously decreased with the increased mass of spay water and the reduced EGR rate. It was helpful to raise the charge density of intake manifold and increase the mass of CH4 entering the cylinder. A small amount of vapor promoted the formation of OH, which was beneficial to accelerating combustion. As the amount of spray water increased and the EGR reduced, the dilution effect of water was enhanced due to the great three-body effect of water. In case#2 with 44 mg injection water and 14.4% EGR, the spray water was used to increase the charge density by cooling the temperature of the manifold, but not enough to inhibit the combustion rate in the cylinder. The water absorbed the heat from the flame front and reduced the temperature of cylinder, which had a positive impact on the decline of NO x emission. Combined with the effect of coupling EGR and PWI on combustion characteristics and emission, case#4 with 176 mg water and 3.6%EGR showed the best engine performance. In general, the combination of EGR and PWI could improve combustion characteristics and lower NO x emissions.